Research on the Influence of the Interaction between Errors on the Statics Load Sharing Characteristic of Gear Split Torque Transmission System - Qibo Wang; Jingwei Ding; Guanghu Jin; Rupeng Zhu (Jixie chuandong)
In order to further understand the relationship between the errors and the load sharing performance of the split torque transmission system， the static model and equation of the system are established for the single input double output gear split torque transmission system. The influence of the interaction between errors on the statics load sharing coefficient of the system is studied， and the orthogonal experiment parameter matching analysis based on the interaction is carried out. The results show that there is interaction between partial backlash and between any two center distance errors， and the optimal combination mode can be obtained to improve the load sharing performance of the system through the parameter matching analysis based on interaction.